Effect of polymer topology on non-covalent polymer-protein complexation: miktoarm versus linear mPEG-poly(glutamic acid) copolymers - Nieto-Orellana, Alejandro; Di Antonio, Marco; Conte, Claudia; Falcone, Franco H.; Bosquillon, Cynthia; Childerhouse, Nick; Mantovani, Giuseppe; Stolnik, Snow (Royal Society of Chemistry, 2017)
Non-covalent polymer-protein conjugation is emerging as a potential route to improve pharmacokinetics and pharmacodynamics of protein therapeutics. In this study, a family of structurally related block copolymers of mPEG2k - poly(glutamic acid) with linear A-B (mPEG2k-lin-polyGA) and miktoarm A-B3 ((mPEG2k-mik-(polyGA)3) structure was synthesised by N-carboxyanhydride (NCA) ring-opening polymerisation to assess the effect of macromolecular topology of the copolymers on polymer-protein complexation. The data illustrate that the synthesised copolymers are capable of complexing a model protein, lysozyme, at optimal pH conditions through non-covalent interactions, with complexation efficiencies depending on the copolymers composition and molecular architecture. In native gel electrophoresis experiments, linear mPEG2k-lin-GA10 copolymer, possessing a short polyanionic polyGA block, shows a low level of complexation, which does not change when the number of polyGA branches of the same size is increased, using a miktoarm mPEG2k-mik-(GA10)3 copolymer. However, enhanced complexation is observed when the same number of ionisable GA units (30) are displayed on a linear macromolecular scaffold; mPEG2k-mik-(GA10)3 vs. mPEG2k-lin-GA30. Again complexation efficiency did not increase when the number of complexing polyGA branches were increased; mPEG2k-lin-GA30 vs. mPEG2k-mik-(GA30)3. Nanoparticle tracking analysis (NTA) showed that the copolymer-protein complexes possessed hydrodynamic diameters in the 50-200 nm range, suggesting a degree of control in the assembly process. Sequestration of lysozyme within polymer complexes resulted in a decrease in its apparent enzymatic activity, which was re-established on the complexes dissociation upon a treatment with competitive complexant. Intrinsic fluorescence and circular dichroism (CD) studies suggested structural conformation of the protein was not altered following complexation with mPEG2k-polyGA copolymers. Taken together, these results provide an initial structure-function relationship for protein-complexing mPEG2k-polyGA copolymers with variable macromolecular topology, opening the way for their future application in biological and biomedical studies.